A synthetic chalcone, 2'-hydroxy-2, 3, 5'-trimethoxychalcone triggers unfolded protein response-mediated apoptosis in breast cancer cells. Issue 1 (1st March 2016) - Lee, Da Hyun; Jung Jung, You; Koh, Dongsoo; Lim, Yoongho; Lee, Young Han; Shin, Soon Young
Highlights: 2'-Hydroxy-2, 3, 5'-trimethoxychalcone (DK143) is a synthetic chalcone derivative. DK143 triggers caspase-dependent apoptosis in various cancer cells. DK143 causes selective ROS accumulation in cancer cells. DK143-induced apoptosis is induced by the ROS-mediated unfolded protein response. Abstract: The primary aim of this study was to find novel chemopreventive agents effective against breast cancer. Endoplasmic reticulum (ER) stress can induce apoptosis through the unfolded protein response (UPR). 2'-Hydroxy-2, 3, 5'-trimethoxychalcone (DK143) is a synthetic flavonoid derivative. The present study provides evidence supporting the role of the UPR in mediating the apoptotic effect of DK143. Treatment with DK143 triggered apoptosis through the activation of the caspase pathway in MDA-MB-231 breast cancer cells without affecting viability of MCF10A non-transformed breast epithelial cells. Further analysis revealed that DK143 produced reactive oxygen species (ROS) in MDA-MB-231 cells, but not in MCF10A cells, and upregulated the expression of ER stress sensors, including GRP78/BiP, IRE1α, CHOP, and Bim in MDA-MB-231 cells. In addition, UPR-related transcription factors, XBP-1 and CHOP, were activated by DK143. Moreover, silencing of IRE1α or CHOP by corresponding siRNA molecules attenuated DK143-induced apoptosis. Furthermore, DK143 suppressed mouse tumor growth in vivo . These results demonstrate that promoting ER stress in breast cancer cells via UPR induction might be a promising strategy for developing new chemotherapeutic or chemopreventive agents for breast cancer.